TANTANGAN TEKNOLOGI DAN PEMANGKU KEPENTINGAN DALAM PEMETAAN PARTISIPATIF: Studi Kasus PLUP+ di Labbo, Indonesia : Technological and Stakeholder Challenges in Participatory Mapping: A Case Study of PLUP+ in Labbo, Indonesia. - Naufal, Naufal; A. Samsu, Andi Khairil (Program Studi Kehutanan Universitas Muslim Maros, 2025)
Participatory mapping faces the dual challenge of generating data that is both valid for formal institutions and accessible to local communities, particularly those living adjacent to forest areas. This study aims to develop a participatory mapping model that integrates geospatial technology with diverse stakeholder needs, identify factors influencing community participation, and evaluate implementation impacts on data validity. Through a qualitative approach and methodological engagement within a participatory action research framework in Labbo Village, South Sulawesi, Indonesia, we developed an Integrated Participatory Land Use Planning (PLUP+) model that combines Web-GIS with microclimate sensors. Data collection methods included in-depth interviews with key actors, focus group discussions, participatory observation, public consultations, and GPS measurements. Results indicate that appropriate technological integration significantly enhances data accuracy and community participation, particularly when aligned with immediate interests such as access to agricultural assistance programs and clarification of land/village boundaries. The model facilitates effective collaboration among stakeholders through a shared platform.Key supporting factors include adequate technological infrastructure and local political support, while unstable political dynamics and digital divides present significant barriers. PLUP+ successfully integrates local knowledge with geospatial technology,empowering communities in sustainable land use planning and natural resource management. This research contributes to bridging the gap between technological innovation and participatory approaches in resource governance, offering a scalable model for similar contexts globally.